Dictionarization and Lexical Variation in Dictionaries of Spanish Neologisms - Adelstein, Andreína (2020)
Fil: Adelstein, Andreína. Universidad Nacional de General Sarmiento. Instituto del Desarrollo Humano; Argentina.